Endocrine therapy for metastatic solid pseudopapillary neoplasm of the pancreas: A case report - Kornietskaya, Anna; Evdokimova, Sevindzh; Kachmazov, Andrei; Fedenko, Alexander.; Bolotina, Larisa; Sidorov, Dmitriy; Volchenko, Nadezhda; Goeva, Natalia; Govaleshko, Anastasia; Kaprin, Andrey (Frontiers in Oncology, 2022)
Solid pseudopapillary neoplasm (SPN) of the pancreas is an extremely rare tumor, associated with favorable prognosis and long-term survival in patients with advanced disease. However, limited data exist on systemic therapy for such patients. Herein, we present a case of a young woman with a history of SPN, who progressed after multiple surgical resections and chemotherapy regimens. The immunohistochemistry (IHC) showed overexpression of estrogen receptors (ER) and progesterone receptors (PR) in tumor tissue. The patient started to receive tamoxifen and showed a durable response to endocrine therapy.